Using Larvae And Adults Of Different Species Of Flies To Detect Certain Homicides (International Journal of Environmental Sciences, 2025)
The current study was conducted at the animal house of the College of Veterinary Medicine, Tikrit University, from September 1, 2024, to January 20, 2025. The study involved three groups of rabbits, each subjected to different methods of euthanasia. The first group was administered gunpowder powder, the second group was administered a solution of tramadol, and the third group was administered a pesticide (toxin). The rabbits were then slaughtered and left for insects to access. Fly larvae of house flies, flesh flies, and blue flies were collected after 3, 6, 8, and 11 days post-mortem, while adults were collected after 13, 15, 18, 21, 25, and 27 days post-mortem. The concentrations of gunpowder, tramadol, and the toxin in the larvae and adults of the flies were measured using HPLC. The results were as follows: The blue fly showed a correlation in numerical data across the days, with concentrations of gunpowder in the larvae exceeding the holding time concentration on days 3 and 11, reaching values of 4.999 and 5.629 µL/gram, respectively. The average adult blue flies recorded the highest concentration of 5.576 µL/gram. For tramadol, the highest concentration recorded among species averages was 6.844 µL/gram. Additionally, the blue fly larvae excelled in recording the highest concentrations throughout the study period, all exceeding the standard holding time. Meanwhile, the adult blue flies recorded tramadol concentrations higher than the holding time concentration throughout the study period, which may indicate this species' ability to retain tramadol traces for a longer duration, as well as its sensitivity to tramadol and effectiveness in detecting it. The larvae of the flesh fly recorded the highest concentration of the toxin as an average over the study period of 9.040 µL/gram, while adult blue flies recorded a significant concentration above the standard holding time concentration of 8.797 µL/gram.